A REVIEW OF ORDER PICKING IMPROVEMENT METHODS - Ong, Johan Oscar; Joseph, Don Thomas (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2014)
As a crucial and one of the most important parts of warehousing, order picking often raises discussion between warehousing professionals, resulting in various studies aiming to analyze how order picking activity can be improved from various perspective. This paper reviews various past researches on order picking improvement, and the various methods those studies analyzed or developed. This literature review is based on twenty research articles on order picking improvement viewed from four different perspectives: Automation (specifically, stock-to-picker system), storage assignment policy, order batching, and order picking sequencing. By reviewing these studies, we try to identify the most prevalent order picking improvement approach to order picking improvement. Keywords: warehousing; stock-to-picker; storage assignment; order batching; order picking sequencing; improvement